2014
DOI: 10.1021/ma501246j
|View full text |Cite
|
Sign up to set email alerts
|

Mediated Competitive Hydrogen Bonding Form Mesoporous Phenolic Resins Templated by Poly(ethylene oxide-b-ε-caprolactone-b-l-lactide) Triblock Copolymers

Abstract: A series of immiscible triple crystalline triblock copolymers, poly(ethylene oxide-b-ε-caprolactone-b-L-lactide) (PEO-b-PCL-b-PLLA), synthesized through sequential ring-opening polymerization, have been blended with phenolic resin. FTIR spectra revealed that the ether groups of the PEO blocks were stronger hydrogen bond acceptors for the OH groups of phenolic resin than were the CO groups of the PCL and PLLA blocks. Curing of phenolic with the templates and hexamethylenetetramine resulted in excluded and conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…12 Another reported application for similar terpolymers is to template phenolic resins while curing. 42 More recently, Chiang et al 13 reported trilayered single crystals of PEO-b-PCL-b-PLLA terpolymers in thin films obtained by solvent-induced crystallization.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…12 Another reported application for similar terpolymers is to template phenolic resins while curing. 42 More recently, Chiang et al 13 reported trilayered single crystals of PEO-b-PCL-b-PLLA terpolymers in thin films obtained by solvent-induced crystallization.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…Using this approach, well-defined mesoporous structures can be obtained since the block copolymer could be self-assembled into different structures through microphase separation connected by covalent bond [18][19][20]. The concept of mediating the hydrogen bonding strength in block copolymer mixtures [21][22][23][24][25][26][27][28][29][30][31][32] to synthesize mesoporous materials has been widely discussed in our previous studies [18,19,[33][34][35]. Using a commercial pluronic-type poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) triblock copolymer as the template is the most widely used approach to preparing mesoporous materials; however, because of the limitation presented by the molecular weight of this kind of triblock copolymer, it is difficult to prepare mesoporous phenolic or carbon with pore size >10 nm [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, extending the A- b -B/C mixtures to A- b -B/C- b -D diblock copolymer mixtures as similar triblock copolymer has also received much interest recently since they provide a simpler approach for the formation of hierarchical self-assembled structures such as three lamellae or core–shell cylinder structures [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In general, the B and C blocks would be miscible through hydrogen bonding interactions, but the A and D blocks are immiscible with each other.…”
Section: Introductionmentioning
confidence: 99%